Endometrial cancer prevention in high-risk women. (May 2020) - Njoku, Kelechi; Abiola, Joanna; Russell, Johanna; Crosbie, Emma J.
Abstract: Endometrial cancer (EC) is the most common gynaecological malignancy, and its incidence is rising alongside the growing prevalence of obesity. Effective risk-reducing interventions hijacking the key mechanisms driving endometrial carcinogenesis may affect EC diagnoses if aimed at those at greatest risk. An understanding of the key risk factors and their role in tumourigenesis is critical in developing such prevention strategies. In this review, we summarise the major risk factors for EC and the evidence for available risk-reducing interventions in high-risk women. We suggest potential prevention strategies and make a case for the need for risk prediction models that identify specific groups of women at a particularly high risk of EC for whom risk-reducing interventions are likely to have a significant impact. Highlights: Endometrial cancer (EC) is rising in incidence in parallel with the obesity epidemic. Obesity-driven EC results from unopposed oestrogen excess, insulin resistance and inflammation. Risk-reducing interventions include bariatric surgery-induced weight loss and continuous oral and intra-uterine progestins. Prophylactic hysterectomy and withdrawal bleeds with cyclical hormones in women with PCOS are other interventions for EC risk reduction.